(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Pacifier is one of the non-nutritive sucking habits. Parent or caregiver often uses pacifier to calm the baby and providescomfortable feeling, especially when going to bed. In general, pacifier is more often used because it is cheap and easy to obtain. But the useof pacifier is still controversial. Possible affect to jaw growth and development, such as dental malocclusion or changes in orodentofacialmorphology, especially if over a long period of time. The use of a pacifier that over one year can affect the occlusion of the primary teethand interfere with the formation of the jaw muscles, causing adverse effects on permanent teeth later.Aim: To determine the effect of using pacifier which if done continuously will cause malocclusion, malrelation, and malposition, as well aschanges in orodentofacial morphology during jaw growth and development in children.Result & Discussion: The use of pacifier in children can be a risk factor for the occurrence of malocclusion, anterior open bite, changes inoverbite and overjet. The development of malocclusion that occurs due to the habit of sucking pacifier depends on its intensity, duration andfrequency. Conclusion: The use of pacifier affects jaw growth and development in children.